Imposing parsimony in cross-country growth regressions - Marek Jarociński (European Central Bank (ECB), 2010)
The number of variables related to long-run economic growth is large compared with the number of countries. Bayesian model averaging is often used to impose parsimony in the cross-country growth regression. The underlying prior is that many of the considered variables need to be excluded from the model. This paper, instead, advocates priors that impose parsimony without excluding variables. The resulting models fit the data better and are more robust to revisions of income data. The positive relationship between measures of trade openness and growth is much stronger than found in the literature.
Keywords: C20; C52; O40; O47; 330; Adaptive Ridge Regression; Bayesian model averaging; Economic Growth; measurement error; Wirtschaftswachstum; Bayes-Statistik; Regressionsanalyse; Messung; Statistischer Fehler; Modellierung; Welt